Letter (copy) : Capture of two British nationals in Madrid - McDonald, Florence
010-0045-001 FEM/KMS/131. Secretary's 17th November, 1936. Rt.Hon. Anthony Eden, M.C., M.P., Secretary of State, Foreign Office, S.W.1. Dear Sir, CAPTURE OF TWO BRITISH NATIONALS IN MADRID. In Sir Walter Citrine's absence I am writing to thank you for your letter of 16th November, informing him that the Burgos authorities have informed Sir H. Chilton that Mr. McMahon and Mr. Boyd, the two members of the Scottish Ambulance Unit who were arrested, are being properly cared for, and will be placed at liberty at whatever point on the frontier that they may select. I know Sir Walter will appreciate the action you have taken in this matter. Yours faithfully, Private Secretary. 292/946/10/48